Emergency nurses' experience of adult basic and advanced life support workstations as a support strategy for clinical practice in the emergency department. (June 2020) - Ireland, Sharyn; Marquez, Marc; Hatherley, Claire; Farmer, Nicole; Luu, Bella; Stevens, Charlotte; Paul, Eldho; Mitra, Biswadev
Abstract: Background: Standards endorsed by the Australian Resuscitation Council in 2014 recommend that healthcare providers trained in cardiopulmonary resuscitation should have their skills refreshed at least annually and for those who infrequently perform resuscitation, more frequent refresher training is advised. Emergency nurses were given the opportunity to attend workstations to refresh their knowledge and skills essential to resuscitation practice. The aim of this manuscript was to report the perception of the nurses' experience following attendance at the workstations. Methods: Lesson plans were developed for six workstations. Consented participants were invited to complete an on-line evaluation survey of their experience following programme participation and at 6-months following programme attendance. Thematic analysis and descriptive statistics were used to report outcomes Results: A total of 143 nurses working in the Emergency Department consented to participate. Following attendance at the workstations, most reported increased knowledge and skills (93.7 %), increased confidence (91.9 %) and that they practiced skills (91.9 %) during workstation participation. At 6-months follow-up the majority of nurses (97.1 %) found the programme to be beneficial and 82 (80.4 %) reported using the knowledge and skills gained from the programme in their clinical practice. Conclusions: Emergency nurses felt more confident in delivering patient care following attendance at the resuscitation workstations. Ongoing education was highly regarded by emergency nurses.